EVALUATION OF THE SKELETAL DIVERGENCE ANGLE ON ORTHOPANTOMOGRAMS - Bernadette Kerekes-Máthé; Zoltán Birtalan; Henrietta Kallos; Krisztina Mártha (Romanian Society of Oral Rehabilitation, 2020)
Facial divergency patterns are important factors for orthodontists. Various growth patterns were associated with dental anomalies, including tooth agenesis. An early identification of these patterns might be critical in preventing severe complications. Orthopantomograms are more often available for dentists than lateral cephalograms. Skeletal divergence angle, which can be used to determine facial divergency patterns, might be measured on orthopantomograms in the lack of cephalograms. Our goal was to find a method to measure skeletal divergence angle on orthopantomograms. A total number of 80 orthopantomogram and cephalogram pairs were used for this study. There were certain differences between the angle values obtained from the cephalograms and the orthopantomograms, but these were not statistically significant. The method described might be helpful for a preliminary determination of the skeletal divergence angle on orthopantomograms in order to decide the next steps and refer the patient to a specialist.